(period) - Stidworthy, Imogen; Matt's Gallery, London (London : Matt's Gallery ; Maastricht : Jan van Eyck Academie, 2012)
This artist's book designed by Jack Fisher focuses on encounters and spaces between languages through the work of Imogen Stidworthy with0contributions from writers Caroline Bergvall, Steven Connor, Mladen Dolar and Alphonso Lingis, and artists Werner Feiersinger, Aglaia Konrad and Willem Oorebee. Taking Stidworthy's artistic practice as a starting point, it traces paths between the images and texts to address related questions. Central to these social and cultural borders which manifest in it. How are we located in the voice and language, and how does this shape our relation to ourselves, our bodies and the spaces we inhabit? Stidworthy's voice runs through the book in the form of video stills, photographs, transcripts and research material which are configured into new images and relationships. Exhibition: Matt's Gallery, London.
boek
Keywords: Stidworthy, Imogen